2020
DOI: 10.18203/2394-6040.ijcmph20202968
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms and associated factors among women exposed to biomass fuel smoke in Sri Lanka: cross sectional study

Abstract: Background: Biomass fuel smoke is a leading cause of indoor air pollution. It is a known risk factor for respiratory diseases. This study was conducted to determine the prevalence of respiratory symptoms and associated factors among women exposed to biomass fuel smoke in Sri Lanka.Methods: Women (n=600) were assessed using questionnaires to determine base line data, cooking fuel use, respiratory symptoms (MRC respiratory symptoms questionnaire) and diagnosed respiratory diseases. Kitchen characteristics were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In this study, it was found that using fuel wood or biomass as a source of energy for cooking is significantly associated with respiratory health problems, which is widely supported by different studies 4 23 43 60. This is because cooking with wood results in incomplete combustion, which produces large quantities of smoke and exposes women to breathable suspended particles, which puts them at a particularly high risk of developing respiratory problems, especially when combined with prolonged periods of time spent in the kitchen.…”
Section: Discussionmentioning
confidence: 64%
“…In this study, it was found that using fuel wood or biomass as a source of energy for cooking is significantly associated with respiratory health problems, which is widely supported by different studies 4 23 43 60. This is because cooking with wood results in incomplete combustion, which produces large quantities of smoke and exposes women to breathable suspended particles, which puts them at a particularly high risk of developing respiratory problems, especially when combined with prolonged periods of time spent in the kitchen.…”
Section: Discussionmentioning
confidence: 64%
“…According to the United Nations Statistics Division (2018), three billion people still use traditional fuel for cooking purposes. Women and children specifically are the two members that are particularly impacted within the community due to the indoor population (Jayaweera et al, 2020). The inefficient cooking practices and fodder, wood, and animal waste are a considerable threat to health and the environment.…”
Section: Fuel Choices and Behavioursmentioning
confidence: 99%
“…Being repetitively exposed to these pollutants can have a substantial impact on the lung function of women and their children. Studies showed that women exposed to biomass fuel have a significantly low FEV 1 /forced vital capacity ratio, together with a higher prevalence of cough, phlegm, wheeze and breathlessness, compared with those not exposed to biomass fuel [89][90][91]. The incidence of women exposed to biomass fuel smoke developing COPD is about 2.4 times higher than those exposed to liquefied petroleum gas [92].…”
Section: Early Origins Of Copdmentioning
confidence: 99%